Prophet of the reformation an exposition of the prophecy of Malachi - Tatford, Frederick Albert, 1901- (Sussex, UK Prophetic Witness, 1972)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Malachi -- commentaries